Development of the Practice of Pharmaceutical Care for Cancer Pain Management in Outpatient Clinics Using the Delphi Method - Zhang, Lu; Ren, Xia-Yang; Huang, Hang-Xing; Huang, Ya-Min; Huang, Ling; Chen, Xiao-Ping; Chen, Yao; Wang, Chen; Xiao, Jian (Frontiers in Pharmacology, 2022)
Background: There exists no broad agreement of experts on the practice of pharmaceutical care for cancer pain management in outpatient clinics. Objectives: This study aimed to use the Delphi consensus process to provide expert recommendations on the practice of cancer pain management in outpatient clinics from the point of view of pharmaceutical care in clinical practice and future clinical trials. Methods: A comprehensive literature review was conducted to draft the initial practice. In this process, 30–40 senior experts from various provinces in China were invited to rank the items of practice during the two Delphi consultations. The definitions of consensus included a combination with an average score of ≥4, the percentage of experts rating the scores at >4 points, and the coefficient of variation of the scores. Results: The expert panel comprised 18 pharmacists, 3 anesthesiologists, 6 oncologists, and 9 nurses. As a result of a comprehensive review, 33 items were initially formed. Among them, the consensus was reached for 27 items after the first Delphi round. The other six items and a total of five items for supplementation entered the second round, among which consensus was reached for eight items and three items were excluded. Expert consensus was achieved on 35 items after two rounds of consultation, which involved the collection of patients’ basic information, comprehensive pain assessment, breakthrough or neuropathic pain assessment, analgesic treatment evaluation, out-of-hospital follow-up, medical records, and evidence-based documents for reference. Conclusion: The final list of 35 items could be employed to develop the practice of pharmaceutical care for cancer pain management in outpatient clinics in China. The practice may aid in the standardization of pharmaceutical care for pain, relieve pain to the greatest extent possible, and enhance the level of pain management in China.